2013
DOI: 10.4103/2229-5178.115518
|View full text |Cite
|
Sign up to set email alerts
|

Necrolytic migratory ulceration

Abstract: Endocrine tumors of the gastroenteropancreatic system associated with specific skin manifestations are rare. We report a 53-year-old female who presented with migratory annular and arcuate ulcers on her limbs. Histopathology was similar to necrolytic erythema family which includes necrolytic migratory erythema (NME). Though initial CT scans were normal, follow up scans revealed multiple mass lesions in the tail of pancreas. Her skin lesions responded to oral zinc sulphate and monthly injections of octreotide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Causes of NME include glucagon-induced cutaneous necrolysis, hypoaminoacidemia-induced epidermal protein deficiency and necrolysis, dietary or metabolic zinc or essential fatty acids deficiency, glucagon-induced inflammatory mediators, and a wide range of malabsorption ( 93 ). Pakran et al ( 36 ) reported a 53-year-old female patient with NME. Her skin lesions responded to oral zinc sulfate and monthly octreotide injections.…”
Section: Endocrine and Metabolic Diseasesmentioning
confidence: 99%
“…Causes of NME include glucagon-induced cutaneous necrolysis, hypoaminoacidemia-induced epidermal protein deficiency and necrolysis, dietary or metabolic zinc or essential fatty acids deficiency, glucagon-induced inflammatory mediators, and a wide range of malabsorption ( 93 ). Pakran et al ( 36 ) reported a 53-year-old female patient with NME. Her skin lesions responded to oral zinc sulfate and monthly octreotide injections.…”
Section: Endocrine and Metabolic Diseasesmentioning
confidence: 99%